2011
DOI: 10.1021/nl2006438
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensitivity of Graphene Edges Decorated with Metal Nanoparticles

Abstract: Graphene is a novel two-dimensional nanomaterial that holds great potential in electronic and sensor applications. By etching the edges to form nanoribbons or introducing defects on the basal plane, it has been demonstrated that the physical and chemical properties of graphene can be drastically altered. However, the lithographic or chemical techniques required to reliably produce such nanoribbons remain challenging. Here, we report the fabrication of nanosensors based on holey reduced graphene oxide (hRGO), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 41 publications
4
119
1
Order By: Relevance
“…[180] Such defective graphene -with abundant edge defects -exhibited a large and selective electronic response toward the detection of hydrogen, particularly when decorated with Pt nanoparticles. [180] In principle, the substrate surface conditions are also suspected to influence the edge of graphene, and hence the sensing properties of the GFET devices especially at nanoscale. [181] GFET based pH sensors measure the protonation and deprotonation at the (functionalized) graphene surface.…”
Section: Gfet Gas and Ion Sensorsmentioning
confidence: 99%
“…[180] Such defective graphene -with abundant edge defects -exhibited a large and selective electronic response toward the detection of hydrogen, particularly when decorated with Pt nanoparticles. [180] In principle, the substrate surface conditions are also suspected to influence the edge of graphene, and hence the sensing properties of the GFET devices especially at nanoscale. [181] GFET based pH sensors measure the protonation and deprotonation at the (functionalized) graphene surface.…”
Section: Gfet Gas and Ion Sensorsmentioning
confidence: 99%
“…Phan et al [25] reported the improvement of sensitivity by controlling the particle sizes and morphologies of noble metals. Moreover, the oxygen-containing functional groups on the graphene surface are very much effective for the adsorption of sensing gases and make the sensor more efficient at sensing much lower concentrations of gases [27]. The significance of these studies was to demonstrate accurate and fast sensing of oxidizing and reducing gases, like NO2 and NH3, respectively, with a higher selectivity.…”
Section: Graphene/noble Metal Hybrid Hydrogen Sensorsmentioning
confidence: 99%
“…[10][11][12][13] Recently, strain has been suggested as another effective approach to tailor the electronic structure, as it is required for nanoelectromechanical systems. [14][15][16] Moreover, it has been predicted theoretically that bending of a ribbon in-plane into a circular arc simulates a magnetic field of 10 T. 17 Tensile (compressive) strain in graphene results in lattice modifications and corresponding phonon mode softening (hardening).…”
mentioning
confidence: 99%